Materiais híbridos argila-poli(metil metacrilato) obtidos através do método grafting - Suzana, Ana Flávia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Some materials formed by an organic phase dispersed in an inorganic phase present new properties that are not limited to the sum of the properties of their separated components, but are the result of the synergism between the phases at molecular level. These materials are known as organic-inorganic hybrids and has received broad scientific attention in recent decades because of its multifunctional nature. As a part of the study of these materials, the surface modification of clay minerals has become lately an important way to improve or create new properties in hybrid materials. The grafting method, for example, consists in the surface reaction between the silanol groups and the reactive groups of the organic compounds (chloride, alkoxide or hydride) which has the function of bind to the inorganic surface and make it compatible with the organic phase, usually a polymer. These organic compounds are referred as coupling agents, since they have the function of coupling to the organic phase with the inorganic one. Thus, the focus of this work was based on nanocomposites organic-inorganic hybrid material obtaining using the grafting method where the inorganic phase is composed by the sodic montmorillonite clay and the organophilizated clay Cloisite® 10A and the organic by poly(methyl methacrylate) (PMMA). The first step of the nanocomposites obtaining was the separation of a fraction of clay particles of uniform size by centrifugation in various aqueous solutions clay; thereby, the distribution of particle diameter was seen through light scattering technique. This stage of the work was intended that the material had more homogeneity at nanoscopic level. This pre-treated clay was functionalized by covalent bonds with molecules of the coupling agent (trimethoxysilyl) propyl methacrylate (TMSM) in their hydroxyl groups. After this procedure, PMMA was added to this medium to obtain the polymer-clay...

Alguns materiais formados por uma fase orgânica dispersa em uma fase inorgânica apresentam propriedades novas, que não se limitam à soma das propriedades de seus componentes separados, mas são decorrentes de sinergismo entre essas fases em nível molecular. Esses materiais são conhecidos como híbridos orgânico-inorgânicos e tem recebido amplo destaque científico nas últimas décadas devido ao seu caráter multifuncional. Como uma vertente do estudo desses materiais, a modificação de superfícies de argilas minerais se tornou uma forma importante de melhorar ou criar novas propriedades em materiais híbridos. O método grafting, por exemplo, consiste na reação de superfície entre os grupos silanóis presentes na argila e os grupos reativos do composto orgânico (cloreto, alcóxido ou hidreto) que tem a função de se ligar a essa superfície inorgânica e torná-la compatível com a fase orgânica, usualmente um polímero. Esses compostos orgânicos são chamados de agentes acopladores, pois têm a função de acoplar a fase orgânica e a inorgânica. Assim, o foco desse trabalho baseou-se na obtenção de materiais híbridos orgânico-inorgânicos nanocompósitos utilizando o método grafting, sendo que a fase inorgânica é composta pela argila montmorilonita sódica e a organofilizada Cloisite® 10A e a orgânica pelo poli(metil metacrilato) (PMMA). A primeira etapa na obtenção dos nanocompósitos consistiu na separação de uma fração da argila com tamanhos uniformes de partículas através da centrifugação de diversas soluções aquosas; desse modo, a distribuição do diâmetro das partículas foi estudado através da técnica de espalhamento de luz. Essa etapa do trabalho teve o intuito de que o material tivesse maior homogeneidade a nível nanoscópico. Essa argila previamente tratada foi funcionalizada através de ligações covalentes com moléculas do agente acoplador...
Keywords: Físico-química; Polimeros; Argila; Termogravimetria; Espectroscopia de raio X; Clay